Transforming Higher Education Curriculum Through OBE-Based Semester Learning Plans Integrated with Mpu Kuturan’s Ethical Framework - Pitriani, Ni Rai Vivien; Fitriani, Luh Putu Widya; Suseni, Komang Ayu (Indonesian Values and Character Education Journal, 2024)
Semester Learning Plans (RPS) oriented toward learning outcomes often overlook the development of students' character. In the context of higher education, the Outcome-Based Education (OBE) approach offers a solution by emphasizing clear and measurable learning outcomes, while the character values of Mpu Kuturan can reinforce students' moral and ethical dimensions. This study aims to develop an OBE-based RPS integrated with Mpu Kuturan’s character values to enhance the quality of higher education. This research adopts a Research and Development (R&D) approach using the ADDIE model (Analyze, Design, Develop, Implement, Evaluate). Data were collected through document analysis, interviews with lecturers, and classroom observations. The research subjects included subject matter experts, policy administrators, teaching practitioners (lecturers), and postgraduate students in Hindu Religious Education. The instruments used included questionnaires, and data were analyzed both qualitatively and quantitatively. The findings indicate that developing an OBE-based RPS integrated with Mpu Kuturan’s character values is highly feasible for implementation in the Master’s Program of Hindu Religious Education. The developed RPS not only enhances curriculum relevance but also strengthens students' commitment to academic ethics and increases their engagement in learning. Thus, this approach can serve as an innovative model for designing higher education curricula based on character values and learning outcomes.